Analysis of Capital Structure and Performance of Banking Sector in Middle East Countries - El-Chaarani, Hani; El-Abiad, Zouhour (International Journal of Economics and Financial Issues, 2019)
Middle East countries during a period of 6 years (between 2011 and 2016). By using 143 banks and 723 observations, the study shows that the capital structure of the banking sector was very volatile during the studied period due to the economic conditions of the region. The results also reveal the existence of positive and significant impacts of total debt and short-term debt on the ROE of the banking sector in Middle East region. However, the results show negative and significant impacts of total debt and short-term debt on the ROA. Additional analysis reveals a positive impact of long-term debt on the ROA ratio. Finally, this study refuses the endogeneity hypothesis of the capital structure and the performance measured by the profitability of the banking sector, and considers that the capital structure design is highly influenced by the decision taken by the international and national regulatory boards. Keywords: Capital Structure, performance, banks, leverage, long and short-term debts. JEL Classifications: G2, G32 DOI: https://doi.org/10.32479/ijefi.7454